A quantitative study of the helminth parasites of the Newfoundland short-finned squid, Illex illecebrosus illecebrosus (LeSueur) (Cephalopoda:Decapoda) - Brown, Elizabeth L.; Threlfall, William (Canadian Journal of Zoology, 1968)
Ommastrephid squid of the subspecies Illex illecebrosus illecebrosus (LeSueur) were obtained during the late summer and early autumn of 1966 and 1967 from numerous areas around the eastern coast of the island of Newfoundland. Helminths of five genera were found, namely, Phyllobothrium sp. and Dinobothrium plicitum (both of which had previously been recorded from this host), Pelichnibothrium speciosum, Scolex polymorphus, and Nybelinia sp. The last three represent new records from this ommastrephid. The incidence of these parasites was tested for correlation with standard length and with sex of the host animal. Annual and seasonal variations in degree of infection were also noted. The greatest number of procercoids encountered were Dinobothrium plicitum. Degree of infection with helminths in 1966 and 1967 was similar (39%:40%) and contrary to earlier published data, infection by cestodes is not always directly correlated with mantle length. Any possible relations between sex of the squid and parasite burden are unclear.